Tailoring adsorption induced switchability of a pillared layer MOF by crystal size engineering. Issue 3 (16th November 2020) - Abylgazina, Leila; Senkovska, Irena; Ehrling, Sebastian; Bon, Volodymyr; St. Petkov, Petko; Evans, Jack D.; Krylova, Svetlana; Krylov, Alexander; Kaskel, Stefan
Abstract : The main factors affecting switchability are identified for DUT-8(Zn): energetics of the host, particle size, and desolvation stress. They influence the flexible behaviour to the same order of magnitude and should be always considered collectively. Abstract : The pillared layer framework DUT-8(Zn) (Zn2 (2, 6-ndc)2 (dabco), 2, 6-ndc = 2, 6-naphthalenedicarboxylate, dabco = 1, 4-diazabicyclo-[2.2.2]-octane, DUT = Dresden University of Technology) is a prototypical switchable MOF, showing characteristic adsorption and desorption induced open phase (op) to closed phase (cp) transformation associated with huge changes in cell volume. We demonstrate switchability strongly depends on a framework-specific critical particle size ( d crit ). Superposed, the solvent removal process (pore desolvation stress contracting the framework) significantly controls the cp/op ratio after desolvation and, subsequently, the adsorption induced switchability characteristics of the system. After desolvation, the dense cp phase of DUT-8(Zn) shows no adsorption-induced reopening and therefore is non-porous for N2 at 77 K and CO2 at 195 K. However, polar molecules with a higher adsorption enthalpy, such as chloromethane at 249 K and dichloromethane (DCM) at 298 K can reopen the macro-sized crystals upon adsorption. For macro-sized particles, the outer surface energy is negligible and only the type of metal (Zn, Co, Ni) controls the DCM-induced gate opening pressure. The node hinge stiffness increases from Zn to Ni as confirmed by DFT calculations, X-ray crystal structural analysis, and low frequency Raman spectroscopy. This softer Zn-based node hinges and overall increased stabilization of cp vs. op phase shift the critical particle size at which switchability starts to become suppressed to even lower values ( d crit < 200 nm) as compared to the Ni-based system ( d crit ≈ 500 nm). Hence, the three factors affecting switchability (energetics of the empty host, ( E op – E cp ) (I), particle size (II), and desolvation stress (III)) appear to be of the same order of magnitude and should be considered collectively, not individually.